Puisi Nikah Sungai dan Nikah Pisau karya Dorothea Rosa Herliany dalam perspektif ekofeminis Mary Daly - Iswadi Bahardur; Putri Dian Afrinda; Rina Sartika (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This research is motivated by the problem of the relationship between women and nature with male power which is reflected poetically by Dorothea Rosa Herliany in two poems entitled "Nikah Sungai" and "Nikah Pisau". Based on that problem, this study aims to describe (a) the power of male patriarchal necrophilia over women; and (b) the attitude of women as an effort to free themselves from the necrophiliac power of men. The research method used is qualitative with descriptive content analysis techniques. The research findings show two things. First, the poems "Nikah Sungai" dan "Nikah Pisau" reflect men's efforts to destroy women's natural reproductive abilities using the power of necrophilia through manipulating various natural resources such as plants, rocks, sand, animal carcasses, soil, and poison as weapons. Second, the attitude of women's resistance to the power of male necrophilia which is reflected by Dorothea in her two poems is manifested in acts of physical violence such as stabbing the heart and tearing the male genitalia.